Gerak Cerdas Lansia : Fisioterapi Komunitas untuk Pencegahan Stroke di Komunitas Alzheimer Solo Raya - Nur Afrina Azra; Rosa Salsa Bila Putri; Jenny Jesica Wenhar; Miftakhul Naela Mafaeza Mukaromah; Choiriyyah Haraf; Arif Prostianto (Health Community Service, 2025)
Indonesia's demographic transition has increased the elderly population and the risk of degenerative diseases such as Alzheimer's and stroke. Both conditions have modifiable risk factors, such as hypertension, diabetes, and lack of physical activity. Community-based interventions that combine health education and structured physical exercise have been shown to reduce the risk of stroke and maintain cognitive function in the elderly. However, accessible and sustainable programs specifically for elderly communities with cognitive impairment, such as the Solo Raya Alzheimer's Community, are still limited. This community service aims to implement a participatory and educational community physiotherapy intervention called “Gerak Cerdas Lansia” (Smart Movement for the Elderly) to increase knowledge about stroke prevention and improve the physical capacity of the elderly. The activity was carried out for two months in 2025 in Banjarsari District, Surakarta, involving 35 elderly people aged ?55 years who had stroke risk factors. The program consisted of health education about stroke and structured physical exercises in the form of breathing exercises, muscle strengthening, balance, coordination, and relaxation. Each session was supervised by a physiotherapist to ensure safety and accuracy of movements. To support sustainability, participants were provided with a guidebook and exercise videos, and community cadres were trained to guide independent activities. The results of the observation showed an increase in participants' understanding of stroke risk factors, increased participation in exercises, and improved physical stability. This program also strengthened community empowerment through the involvement of cadres and the provision of educational media. “Gerak Cerdas Lansia” proves that a community-based physiotherapy approach is feasible to support stroke prevention and create healthier and more independent elderly people. Keywords: Stroke Prevention, Elderly, Health Education   ABSTRAK Transisi demografi Indonesia telah meningkatkan populasi lansia dan risiko penyakit degeneratif seperti Alzheimer dan stroke. Kedua kondisi ini memiliki faktor risiko yang dapat dimodifikasi, seperti hipertensi, diabetes, dan kurangnya aktivitas fisik. Intervensi berbasis komunitas yang menggabungkan edukasi kesehatan dan latihan fisik terstruktur terbukti dapat menurunkan risiko stroke dan mempertahankan fungsi kognitif lansia. Namun, program yang mudah diakses dan berkelanjutan khusus untuk komunitas lansia dengan gangguan kognitif seperti Komunitas Alzheimer Solo Raya masih terbatas. Pengabdian masyarakat ini bertujuan menerapkan intervensi fisioterapi komunitas partisipatif dan edukatif bernama “Gerak Cerdas Lansia” untuk meningkatkan pengetahuan pencegahan stroke dan kapasitas fisik lansia. Kegiatan dilaksanakan selama dua bulan pada tahun 2025 di Kecamatan banjarsari, Surakarta, dengan melibatkan 35 lansia berusia ?55 tahun yang memiliki faktor risiko stroke. Program terdiri atas edukasi kesehatan mengenai stroke dan latihan fisik terstruktur berupa latihan pernapasan, penguatan otot, keseimbangan, koordinasi, serta relaksasi. Setiap sesi didampingi fisioterapis untuk menjamin keamanan dan ketepatan gerakan. Untuk mendukung keberlanjutan, peserta dibekali buku panduan dan video latihan, serta kader komunitas dilatih untuk memandu kegiatan mandiri. Hasil observasi menunjukkan peningkatan pemahaman peserta mengenai faktor risiko stroke, peningkatan partisipasi dalam latihan, serta perbaikan stabilitas fisik. Program ini juga memperkuat pemberdayaan komunitas melalui pelibatan kader dan penyediaan media edukatif. “Gerak Cerdas Lansia” membuktikan bahwa pendekatan fisioterapi berbasis komunitas layak diterapkan untuk mendukung pencegahan stroke dan menciptakan lansia yang lebih sehat dan mandiri. Kata kunci: Pencegahan stroke, lansia, Edukasi Kesehatan